Learning and memory formation in zebrafish: Protein dynamics and molecular tools - Reemst, Kitty; Shahin, Heba; Shahar, Or David (Frontiers in Cell and Developmental Biology, 2023)
Research on learning and memory formation at the level of neural networks, as well as at the molecular level, is challenging due to the immense complexity of the brain. Zebrafish have a, smaller and more accessible brain than that of mammals, allowing imaging of the entire brain during behavioral manipulations in larval stages. The zebrafish as a genetically tractable model organism, can overcome many of the current challenges of studying molecular mechanisms of learning and memory formation. Recent years have seen an extensive increase in published brain research describing the use of zebrafish for the study of learning and memory. Nevertheless, due to the complexity of the brain comprising many neural cell types that are difficult to isolate, it has been difficult to elucidate neural networks and molecular mechanisms involved in memory formation in an unbiased manner, even in zebrafish. Therefore, data regarding the identity, location, and intensity of nascent proteins during memory formation is still sparse and our understanding of the molecular networks remains limited, indicating a need for new techniques. Here, we review recent progress in establishing learning paradigms for zebrafish and the development of methods to elucidate neural and molecular networks of learning. We describe various types of learning and highlight directions for future studies, focusing on molecular mechanisms of long-term memory formation and promising state-of-the-art techniques such as cell-type-specific metabolic labeling.